HEALTH CARE TECHNOLOGY FOR TRAINING MASTERS OF SOCIAL WORK IN THE CONDITIONS OF INFORMATIZATION OF EDUCATION (Psychology Travelogs, 2022)
Professional education is determined by the needs of society and the individual. Therefore, we consider the training of future social workers (masters) in the conditions of informatization of education as a whole continuous system that includes other subsystems, the result of which is the acquisition by future specialists of a set of systematized knowledge, abilities and skills that will contribute to independent and responsible solving of research and practical tasks, skill in the field of health care; creative use of scientific achievements in the field of culture and social work.Modern health care technology is based on the best examples of domestic and foreign experience, it takes into account the individual requests of students of higher education and teachers. This is facilitated by legislation and the theory and practice of scientific research in this field. Modern forms and methods, both traditional and innovative, stimulating work in this direction and the appropriate material and technical base of higher education institutions are powerful tools for the implementation of measures within the limits of technology. We cannot ignore the methods of monitoring the implementation of plans in this direction and orders. At the same time, monitoring of implementation should not be punitive, but recommendatory in nature, which will contribute to the formation of trusting relationships between participants in the educational process.
Keywords: professional education; social worker; culture; work